ChemInform Abstract: Biomass Pyrolysis‐ A Review of Modelling, Process Parameters and Catalytic Studies. Issue 9 (February 2016) - Sharma, Abhishek; Pareek, Vishnu; Zhang, Dongke
Abstract: Review: 162 refs.